Analisis Strategi Pemasaran Jasa Instalasi WiFi dalam Perspektif Ekonomi Islam: Studi Kasus PT RST.Net - Arwani Arwani; Tenda Budiyanto (LPPM IAI Pangeran Dharma Kusuma Segeran Indramayu, 2026)
Background: The rapid expansion of digital infrastructure necessitates ethical marketing frameworks, yet the integration of Islamic economic principles into digital service marketing remains underexplored. Purpose: This study analyzes the marketing strategy of WiFi installation services at PT RST.Net through the lens of Islamic economics, specifically examining the alignment of the marketing mix with Sharia principles. Methods: Employing a qualitative case study design, data were collected via in-depth interviews with purposively selected informants (1 owner, 2 technicians, 5 customers), direct observation, and documentation. Data validity was ensured through source and method triangulation, and analyzed using the Miles, Huberman, and Saldaña interactive model. Results: PT RST.Net’s marketing mix (4P) demonstrates strong empirical alignment with Islamic principles: Shiddiq (honesty) in transparent promotion, Adl (justice) in equitable pricing, and Maslahah (public benefit) in strategic rural service distribution. Novelty: This study proposes a novel